Characteristics of adults with a medical cannabis license, reasons for use, and perceptions of benefit following medical cannabis legalization in Oklahoma - Darla E. Kendzor; Sarah J. Ehlke; Laili Kharazi Boozary; Michael A. Smith; Amy M. Cohn (Preventive Medicine Reports, 2022)
Little is known about the risks and benefits associated with medical cannabis legalization. The current study was an online panel survey of adult Oklahomans recruited between September and October 2020 (N = 1898). Respondents with and without a medical cannabis license were compared on sociodemographic, substance use and health characteristics, and sub-analyses focused on the characteristics of licensed and unlicensed past 30-day cannabis users. Among all participants, 19.34% (n = 367) reported that they had a medical cannabis license, and 35.73% (n = 676) reported past 30-day cannabis use. Licensees were more likely to be younger (i.e., 18–35 years of age; p = 0.001), identify as a sexual minority (p < 0.001), and report past 30-day cannabis, cigarette, alcohol, and prescription opiate use (all p’s ≤ 0.003). Licensed participants most commonly reported medically-recommended cannabis use for anxiety (42.51%), depression (33.24%), sleep problems (26.98%), chronic pain (24.25%), and arthritis (12.81%). The likelihood of medically-recommended cannabis use for anxiety, depression, and chronic pain differed by age group (all p’s ≤ 0.028). Licensees were most likely to perceive that cannabis delivered “very much/extreme” relief from anxiety (78.57%), sleep problems (76.30%), nausea/vomiting (70.00%), and depression (67.05%). Compared to licensed past 30-day cannabis users (n = 308), unlicensed users (n = 368) were more likely to be non-White, to have ≤ high school education, to report an annual household income <$30,000, and to report current smoking (all p’s ≤ 0.027). Findings provide initial information about the personal characteristics associated with having a medical cannabis license in Oklahoma, the reasons for medical cannabis use, and the perceived medical benefits.